Clinical anatomy of the base of the skull: meninges, inter meningeal spaces and craniocerebral topography (Journal of Science-Innovative Research in Uzbekistan, 2023)
The article of the clinical anatomy of the base of the skull is pivotal in comprehending the intricate structures that govern neurological function and safeguard vital neural pathways. This exploration delves into the detailed anatomy of the meninges, intermeningeal spaces, and craniocerebral topography, shedding light on their clinical relevance